2021
DOI: 10.1002/brb3.2316
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture reactivates estrogen receptors to restore the neuroprotective effect of estrogen against cerebral ischemic stroke in long‐term ovariectomized rats

Abstract: Background: Stroke is a sexually dimorphic disease and a leading cause of death and disability. Estrogen replacement therapy (ERT) confers beneficial neuroprotective effects if administered within a widely accepted time window called the "critical period." However, very few studies have explored the idea of modulating the critical period to enable long-term post-menopausal women to regain more benefits from estrogen therapy. Here, motivated by previous findings that electroacupuncture could both alter estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This observation indicated that the effective dose range of E2 for neuroprotection was narrow, probably due to the different receptors and signaling pathways activated by different concentrations of E2. Previous reports have shown that E2 shows neuroprotective effects primarily through ERβ and CPER [52][53][54]. In the microglia, the activation of NF-κB plays a critical role in the production of proin ammatory cytokines, leading to the neurotoxic effect [55].…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicated that the effective dose range of E2 for neuroprotection was narrow, probably due to the different receptors and signaling pathways activated by different concentrations of E2. Previous reports have shown that E2 shows neuroprotective effects primarily through ERβ and CPER [52][53][54]. In the microglia, the activation of NF-κB plays a critical role in the production of proin ammatory cytokines, leading to the neurotoxic effect [55].…”
Section: Discussionmentioning
confidence: 99%
“…26 It is reported in previous data that estrogen has a neuroprotective effect on ischemic stroke. 27 However, the level of menopause and estrogen decline rapidly in elder women It has been demonstrated from epidemiological studies that the majority of strokes in postmenopausal women are more severe, lead to poorer psychological outcomes, and result in higher rates of disability. 28 A recent study of the effect of sex on the outcome of mechanical thrombectomy in basilar artery occlusion (BAO) showed that women achieved comparable functional outcomes compared with men after undergoing mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…26 It is reported in previous data that estrogen has a neuroprotective effect on ischemic stroke. 27 However, the level of menopause and estrogen decline rapidly in elder women It has been demonstrated from epidemiological studies that the majority of strokes in post-menopausal women are more severe, lead to poorer psychological outcomes, and result in higher rates of disability. 28…”
Section: Discussionmentioning
confidence: 99%
“…To date, three types of ERs have been identified: ERα, ERβ, and G-protein coupled receptors ( 37 39 ). Reportedly, estrogen mediates its effects via two signaling pathways ( 40 ). The first is the genomic pathway, which involves ERα and ERβ.…”
Section: Downstream Signaling Pathways Of Estrogenmentioning
confidence: 99%